Mortality, Work and Migration. A Consideration of Age-specific Mortality from Tuberculosis in Scotland, 1861-1901 - Alice Reid; Eilidh Garrett (Historical Life Course Studies)
This paper provides an examination into some of the most enduring debates regarding tuberculosis mortality during the nineteenth century: those related to gender, geographic and temporal variations. We use populations reconstructed from individual census and civil register data for the period 1861 to 1901, comparing a growing urban area with a declining rural area, both with around 20,000 inhabitants in 1861. Our analysis shows that among young adults tuberculosis was linked to excess female mortality in the urban area and excess male mortality in the rural area. We demonstrate that in the town textile workers of both genders had particularly high mortality from tuberculosis, and that the only reason for higher overall female mortality was the predominance of young women in the textile labour force. We show that the age and gender-specific pattern of mortality in the rural area is consistent with higher male than female out-migration together with return migration of those who had contracted the disease elsewhere and needed care during their lengthy illness. We argue that the observed patterns are difficult to reconcile with the ‘bargaining-nutrition’ account of gendered patterns in tuberculosis mortality, and that they provide little support for nutrition as a key influence on the disease. However, our findings do reinforce Andrew Hinde’s recent argument that geographical patterns in sex-specific tuberculosis mortality rates were largely determined by migration patterns, and we discuss the implications of this for our understanding of the decline of the disease over the late nineteenth century.